2008
DOI: 10.1016/j.jsat.2006.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of major depressive disorder and attention-deficit/hyperactivity disorder on the outcome of treatment for cocaine dependence

Abstract: Co-occurring psychiatric disorders have been associated with poor prognosis among substance dependent patients, but few studies have examined this association among patients with cocaine dependence (CD). Baseline characteristics and treatment outcome were compared between cocainedependent patients with major depression (MDD) (N = 66), attention-deficit/hyperactivity disorder (ADHD) (N = 53), or cocaine dependence without comorbid disorders (CD alone) (N = 48), who had been randomized to the placebo arms of cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 54 publications
0
25
1
Order By: Relevance
“…Reasons for this include issues such as lack of staff awareness, ability, or willingness or the lack of clinical resources where clinics are understaffed and staff are overburdened (Flynn & Brown, 2008;Levin et al, 2008). In addition, ADHD is characterized by impulsivity, restless, inattentive, and hyperactive behaviors-symptoms that often mimic those of substance use disorder (SUD; Barkley, 1998;Davidson, 2008;Levin et al, 2008). For these and other reasons, ADHD is frequently unidentified in adulthood, especially in substance abuse treatment (Biederman, Wilens, Mick, Spencer, & Faraone, 1999;Katusic et al, 2005;Mueser, Noordsy, Drake, & Fox, 2003).…”
Section: N 2001 the Substance Abuse And Mental Health Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Reasons for this include issues such as lack of staff awareness, ability, or willingness or the lack of clinical resources where clinics are understaffed and staff are overburdened (Flynn & Brown, 2008;Levin et al, 2008). In addition, ADHD is characterized by impulsivity, restless, inattentive, and hyperactive behaviors-symptoms that often mimic those of substance use disorder (SUD; Barkley, 1998;Davidson, 2008;Levin et al, 2008). For these and other reasons, ADHD is frequently unidentified in adulthood, especially in substance abuse treatment (Biederman, Wilens, Mick, Spencer, & Faraone, 1999;Katusic et al, 2005;Mueser, Noordsy, Drake, & Fox, 2003).…”
Section: N 2001 the Substance Abuse And Mental Health Servicesmentioning
confidence: 99%
“…Investigators have found that up to 50% of individuals with ADHD symptoms in childhood developed SUD (Davids & Gastpar, 2003;Sullivan & Rudnik-Levin, 2001). Other investigators examining the relationship between childhood ADHD and the development of SUD have concluded that adults with a childhood history of ADHD were more likely to develop SUD than those individuals without childhood ADHD (Levin et al, 2004(Levin et al, , 2008Wilens & Fusillo, 2007).…”
Section: N 2001 the Substance Abuse And Mental Health Servicesmentioning
confidence: 99%
“…The authors point to certain other atypical antipsychotic drugs that might prove useful in reducing alcohol and drug problems in populations with co-occurring disorders; additional rigorous studies are needed to determine the efficacy of these medications when prescribed for addicted patients with schizophrenia and other co-occurring severe mental disorders. Levin et al (2008) report on a study of cocainedependent subjects drawn from those who had been randomized into the placebo arms of three medication trials (venlafaxine, methylphenidate, and gabapentin). Subjects were placed in three groups: one group had co-occurring major depression, the second group had co-occurring attention-deficit/hyperactivity disorder, whereas the third group had no co-occurring mental disorder.…”
Section: Treatment Models and Strategiesmentioning
confidence: 99%
“…Furthermore, although data available in the medical literature did not allow the stratification by affective disorders in our metaanalysis, the only study that stratified by affective disorder did show better response to carbamazepine in this subgroup of population (Brady et al, 2002). A similar stratification was described for other comorbid disorders, such as hyperactivity and personality disorder (Ford et al, 2009;Kollins, 2008;Levin et al, 2008). Despite the very limited data, this information could be taken into account when planning future studies.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, the frequency of the follow-up visits and route of cocaine administration (sniffing, "crack," IV) vary among studies. Differences in the use of other drugs as alcohol or cannabis and the presence of other psychiatric comorbid disorders very frequently in cocaine-dependent subjects (Aharonovich et al, 2006;Levin et al, 2008) might explain in part the lack of efficacy found (Aharonovich et al, 2006;Levin et al, 2008). The patterns of cocaine use, including the frequency and route of administration, have been previously described as relevant conditions for outcomes (Ahmadi et al, 2009;Kampman et al, 2002).…”
Section: Discussionmentioning
confidence: 99%